Caraṇarekhā taba - Basu, Krshṇā, 1930- (Ānanda, 1982)
On the activities of the Indian nationalist leader Subhas Chandra Bose, 1897-1945, in Southeast Asia, 1943-1945; based on the author's travels in the region.